The Impact of Debt Financing on Profitability: Insights from Georgian Wine Producers - Kasradze, Tea; Gikorashvili, Papuna (Journal of Cultural Analysis and Social Change, 2026)
This study investigates the impact of debt financing on the profitability of Georgian wine producers between 2019 and 2023. Utilizing an unbalanced panel dataset derived from financial statements, Fixed Effects (FE) panel regression models were employed to control for unobserved firm heterogeneity, thereby enhancing the robustness of the findings. The analysis specifically focused on the relationship between the Debt-to-Assets ratio and two key profitability metrics: Net Profit Margin (NPM) and Return on Assets (ROA). The results consistently demonstrate a robust and statistically significant negative correlation between leverage and profitability, even after accounting for firm-specific effects and time shocks. Specifically, the Fixed Effects models indicate that a 10% increase in the Debt-to-Assets ratio is associated with an approximate decrease of 1.5 percentage points in Net Profit Margin and 0.9 percentage points in ROA. Furthermore, formal testing for a non-linear (inverted-U) relationship yielded statistically insignificant results. This suggests that the costs associated with debt consistently outweigh any potential tax shield or disciplinary benefits across all observed leverage levels. This finding strongly supports the Pecking Order Theory and underscores the significant "double burden" faced by the industry due to high capital intensity and the high cost of debt in an emerging market.